Altered Fluorescence of Buccal Cells as a Candidate Biomarker for Areca Nut Chewing. (1st June 2020) - Biggs, Laura A. F.; Franke, Adrian A.; Farrar, Christine E.
Abstract: Background : Betel nut is used by an estimated 600 million people globally and is the 4th most widely used psychoactive substance in the world. Its use has been shown to cause oral and esophageal cancers. Therefore, cessation programs are needed in which an effective biomarker can be employed. Objectives : Buccal cells are highly exposed to the betel nut during its use and are also easy to collect. However, it is unknown if there are significant changes to these cells upon exposure or how long any changes may last as the turnover of buccal cells is relatively fast. We sought to determine if optical changes could be detected on buccal cells after exposure to betel nut and if detected, how long these changes were sustained. Methods : Flow cytometry was employed to determine whether fluorescence intensities differ between buccal cells exposed to betel nut and naïve cells. We further characterized the optical signature of buccal cells exposed to betel nut and other polyphenol-rich substances using lambda scans performed on a laser scanning confocal microscope. Results : We demonstrate that the fluorescence of betel nut exposed cells is greater than that of cells exposed to other optically active compounds such as polyphenol-rich foods. We also demonstrate that the fluorescence spectra of betel nut quid exposed cells are distinct from that of cells exposed to other polyphenol-rich substances. Conclusions : We conclude that detecting the altered fluorescence of buccal cells following exposure to betel nut quid may serve as a candidate biomarker for betel nut quid use.